Kontribusi Usaha Budidaya Jamur Sawit dalam Memenuhi Kebutuhan Ekonomi Keluarga di Kelurahan Sawah Lebar Kota Bengkulu: Perspektif Ekonomi Islam - Muhammad Yusuf Mahmudi; Khairiah Elwardah; Uswatun Hasanah (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
This study aims to analyze the contribution of oil palm mushroom cultivation in meeting family economic needs and to examine business practices from an Islamic economic perspective. This research employs a qualitative descriptive approach with field research methods. Data were collected through observation, in-depth interviews, and documentation. The results indicate that the business significantly contributes to fulfilling family economic needs, especially primary (daruriyah) needs, while also supporting secondary (hajiyah) and partially tertiary (tahsiniyah) needs. Furthermore, the business practices reflect Islamic economic values such as honesty, responsibility, hard work, and sustainable resource utilization.